A diary study of the impression management strategies utilised by industrial and organisational psychology interns - Nasreen A. McGowan; Lusanda Sekaja (SA Journal of Industrial Psychology, 2022)
Orientation: When interns enter a new workplace, they are compelled to create and maintain a good impression through a range of image-enhancing behaviours. Impression management strategies can help interns to do this.